2003
DOI: 10.1556/avet.51.2003.3.14
|View full text |Cite
|
Sign up to set email alerts
|

Energy imbalance related predisposition to mastitis in group-fed high-producing postpartum dairy cows

Abstract: The energy imbalance related predisposition to mastitis was studied in group-fed postpartum dairy cows (n = 333) kept in 4 large-scale units and producing milk of low somatic cell count (SCC). Blood samples were taken on Days 1-3 after calving for assaying some metabolites and hormones related to the negative energy balance (NEB). If mastitis was diagnosed later, aseptic milk samples were taken to identify the pathogens. Considering pathogen types [contagious pathogens: Staphylococcus (S.) aureus, Gram-positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 35 publications
3
24
0
Order By: Relevance
“…The most common organisms isolated were Escherichia coli and Klebsiella spp accounting for 70.59% of the isolates. This could have been due to hyperketonaemia present during this phase of production as has been reported previously (Harmon, 1984;Janosi et al, 2003;Huszenicza et al, 2004). The low level of hygiene in the cow sheds and practised by the workers as observed in this study could also have led to the high incidence of clinical coliform mastitis (Elbers et al, 1998).…”
Section: Discussionsupporting
confidence: 64%
“…The most common organisms isolated were Escherichia coli and Klebsiella spp accounting for 70.59% of the isolates. This could have been due to hyperketonaemia present during this phase of production as has been reported previously (Harmon, 1984;Janosi et al, 2003;Huszenicza et al, 2004). The low level of hygiene in the cow sheds and practised by the workers as observed in this study could also have led to the high incidence of clinical coliform mastitis (Elbers et al, 1998).…”
Section: Discussionsupporting
confidence: 64%
“…Cows with subclinical ketosis (BHBA .1000 or 1200 mmol/l) during the first 1 to 2 weeks after calving are at greater risk for diseases, that is, metritis ), leftdisplaced abomasum (LeBlanc et al, 2005) and a greater incidence and severity of mastitis (Kremer et al, 1993;Janosi et al, 2003). Several studies have identified potential mechanisms associated with the impairment of the cellular immune function by increased media concentrations of ketones (Franklin et al, 1991;Detilleux et al, 1995).…”
Section: Ketonesmentioning
confidence: 99%
“…Samples were assayed for leptin with a ruminant-specific 125 I-RIA of Delavaud et al (2000Delavaud et al ( , 2002 with some modification (Kulcsár et al, 2005), as well as for cortisol and P 4 with 3 H-RIA methods described in our earlier works (Nagy et al, 1998;Jánosi et al, 2003;Kulcsár et al, 2005). Neutralised acid-ethanol extracts of plasma were analysed for IGF-1 using a heterologous 125 I-RIA system modified for bovine samples (Nikolic et al, 2001), after validating this assay for ovine plasma without any further changes (sensitivity: 0.20 nmol/l, intra-and interassay CVs: ≤ 6.2 and ≤ 12.0%).…”
Section: Handling Of Samples Laboratory Procedures Statisticsmentioning
confidence: 99%
“…The non-responders had lower IGF-1 and leptin levels than those ovulated after this treatment. It was concluded that the subclinical form of ovine ketosis is characterised by complex endocrine altera-In postpartum dairy cows the negative energy balance (NEB) and mainly its decompensation (ketosis, fatty liver disease) are characterised by numerous metabolic changes, which are known to postpone the resumption of cyclic ovarian function, impair the quality of oocyte, and diminish the capacity of intrauterine and intramammary antimicrobial defence mechanisms, predisposing the affected animal to puerperal metritis and mastitis (Wensing et al, 1997;Chilliard et al, 1998;Suriyasathaporn et al, 2000;Jánosi et al, 2003;Veerkamp et al, 2003). A lower ratio of insulin to glucagon and growth hormone has been demonstrated to act as the main endocrine factor (Sartin et al, 1988) in the pathogenesis of bovine ketosis.…”
mentioning
confidence: 99%